2018
DOI: 10.1007/s11605-018-3894-7
|View full text |Cite
|
Sign up to set email alerts
|

Distal Pancreatectomy with Celiac Axis Resection (DP-CAR) for Pancreatic Cancer. How I do It

Abstract: Approximately 30% of all pancreatic cancer patients have locally advanced (AJCC stage 3) disease. A sub-group of these patients—where the cancer only involves the celiac axis—may benefit from distal pancreatectomy with celiac axis resection (DP-CAR). Previous studies have shown that DP-CAR offers a survival benefit to a selected group of patients with otherwise unresectable pancreatic cancer, when performed by experienced pancreatic cancer treatment teams at high-volume centers. This article proposes a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 35 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…In case of pancreatic body cancer with involvement of the celiac trunk, a distal pancreatectomy with celiac artery resection (DP-CAR or Appleby procedure) may be performed. We previously described the details of this procedure elsewhere [82]. DP-CAR combined with (neo)adjuvant therapy is associated with an 18–19 months overall survival, according to a recent systematic review and retrospective international series [83,84].…”
Section: Resultsmentioning
confidence: 99%
“…In case of pancreatic body cancer with involvement of the celiac trunk, a distal pancreatectomy with celiac artery resection (DP-CAR or Appleby procedure) may be performed. We previously described the details of this procedure elsewhere [82]. DP-CAR combined with (neo)adjuvant therapy is associated with an 18–19 months overall survival, according to a recent systematic review and retrospective international series [83,84].…”
Section: Resultsmentioning
confidence: 99%
“…We chose to perform preoperative CHA embolization to precondition the liver in arterial blood supply solely via the GDA, as is the rule in some centers [ 9 , 13 , 17 ]. Indeed, at exploration we found that the GDA was unusually wider and the blood flow through the PHA was normal.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, at exploration we found that the GDA was unusually wider and the blood flow through the PHA was normal. However, preoperative CHA embolization is not performed in several other high-volume pancreatic centers [ 13 ]. In a recent comparative study [ 7 ], no advantage was documented in 23 patients with CHA embolization before DP-CAR over 8 without.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure relies on the blood supply to PHA from GDA through the preserved pancreaticoduodenal arcade. This collateral channel can be made the dominant supply to biliary system, liver and pancreatic head by embolization of celiac origin and left gastric artery if deemed necessary .…”
Section: Pancreatic Surgerymentioning
confidence: 99%